Monitoramento da integridade estrutural a partir de sensoriamento de baixo-custo: projeto e desenvolvimento de bancada experimental integrada a plataforma de computação em nuvem - Vasconcelos, João Pedro Castro (Universidade Federal de São Carlos, 2023)
Structural Health Monitoring (SHM) has been a widely used tool, as it offers greater longevity to structures. Technologies using vibration as a parameter for this monitoring are proving to be efficient and several research topics in this field are being developed. However, the use of sensors for monitoring structures implies in a high cost, which is the main limitation regarding the feasibility of applying structural integrity monitoring on a larger scale. With the evolution in accuracy and reliability of low-cost sensors and rapid prototyping boards, their implementation in the industry is increasingly being studied. In the current work, a workbench was designed and developed with flexible materials and a simple design, where sensors and a rapid prototyping board were installed, responsible for transmitting the data to a digital platform. Measurements were made on the experimental bench while excited by vibrations, then damage was generated to the bench and new measurements were taken. With this, it was possible to simulate an application of SHM with low-cost sensors and equipment to analyse the behaviour of the data obtained in the proposed damage scenarios. At the end of the study, the established damage indices were sensitive to variations of the damage caused to the bench, demonstrating the potential for an efficient application of the proposed experiment for a structural health monitoring practical model.
Structural health monitoring with low-cost sensing: Design and development of an experimental bench integrated with a cloud computing platform
Keywords: SHM; Vibrações Mecânicas; Sensoriamento de baixo custo; Monitoramento de Saúde Estrutural; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS